Correlation of CYP2B6-516G>T polymorphism with plasma efavirenz concentration and depression in HIV-infected adults in Northern Thailand - Aurpibul,L. (Bentham Science Publishers B.V., 2015)
Background: Single nucleotide polymorphism of the hepatic cytochrome P450 isoenzyme 2B6 (CYP2B6) gene is a cause of variation in plasma efavirenz (EFV) concentrations. We aimed to determine the allelic distribution of CYP2B6 gene, plasma levels of EFV, the prevalence of clinical depression, and their correlations in northern Thai population. Methods: This was a cross-sectional study of HIV-infected patients on EFV-containing antiretroviral regimens for ≥48 weeks. A single blood specimen was collected for determination of the mid-dose plasma EFV concentration and CYP2B6-516G>T polymorphism. The presence and severity of depression were assessed. Results: One hundred patients were enrolled [mean age (± SD) was 41.81 ± 8.44 years, mean CD4 lymphocyte count 462 ± 193 cells/ul]. The genotype CYP2B6-516 guanine/guanine (G/G), guanine/thymidine (G/T), and T/T were found in 49%, 37%, and 14% of patients, respectively. The allele frequency of CYP2B6-516 G to T replacement was 32.5%. The median plasma EFV concentration was 2,616 ng/mL (IQR 1,851-3,742); 79% had EFV plasma concentrations from 1,000 to 4,000 ng/mL. The mean EFV concentrations for those with G/G, G/T and T/T genotypes were 2,082±630, 3,166±1,074, and 11,196±6,265 ng/mL, respectively (p<0.01). CYP2B6-516G>T polymorphism was the only factor associated with high plasma EFV levels. Nineteen patients had depression; 13 of 18 (72%) with mild and one with major depression had normal plasma EFV level. A weak correlation between plasma EFV concentrations and depression scores was observed (p=0.009, R2=0.059). Conclusions: The prevalence of CYP2B6-516G>T polymorphism in northern Thai population is high and strongly associated with inter-individual drug levels variation. © 2012 Bentham Science Publishers.